الرقمنة وعلاقتها بتحسين الخدمات الجامعية للطلبة المقيمين - برواين, خيرة إيمان (كلية العلوم الاجتماعية, 2025)
تهدف هذه الدراسة إلى الكشف عن العلاقة بين الرقمنة وتحسين الخدمات الجامعية المقدمة للطلبة لدى عينة متكونة من (62) طالب و طالبة متمدرسين في السنة الثالثة ليسانس والسنة الأولى والثانية ماستر بجامعة عبد الحميد بن باديس بولاية مستغانم، اختبرت العينة بطريقة قصدية ،وتم إتباع المنهج الوصفي بالإعتماد على استبيان الرقمنة والخدمات الجامعية من تصميم الطالبة وبعد التحقق من الخصائص السيكومترية المتمثلة في الصدق والثبات تم معالجة البيانات المتحصل عليها احصائيا بالاعتماد على برنامج SPSS27 تم تحليل النتائج ، وتوصلت الباحثة في هذه الدراسة إلى النتائج التالية: -أولا الفرضية الرئيسية والتي تنص على وجود علاقة ذات دلالة احصائية بين الرقمنة والخدمات الجامعية. -أما بالنسبة الفرضيات الفرعية والتي تحققت كما يلي: 1-توجد علاقة ذات دلالة إحصائية بين الرقمنة وتحسين خدمات التسجيل الأكاديمي. 2- توجد علاقة ذات دلالة إحصائية بين الرقمنة وتحسين خدمات الايواء والاطعام. 3- توجد علاقة ذات دلالة إحصائية بين الرقمنة وتحسين خدمات النقل والمنحة الجامعية This study aims to uncover the relationship between digitization and the improvement of university services provided to students, based on a sample consisting of (62) male and female students enrolled in the third year of the Bachelor's degree and the first and second years of the Master's degree at Abdelhamid Ben Badis University in the Wilaya of Mostaganem. The sample was selected intentionally, and the descriptive methode was followed, relying on a digitization and university services questionnaire designed by the student. After verifying the psychometric properties, represented by validity and reliability, the collected data were statistically processed using the SPSS program, and the results were analyzed. The researcher reached the following conclusions in this study: • Firstly, the main hypothesis, which states that there is a statistically significant relationship between digitization and university services. • As for the sub-hypotheses, they were confirmed as follows: 1. There is a statistically significant relationship between digitization and the improvement of academic registration services. 2. There is a statistically significant relationship between digitization and the improvement of housing and catering services. 3. There is a statistically significant relationship between digitization and the improvement of transportation and university grant services.
دراسة ميدانية بكلية العلوم الاجتماعية بجامعة عبد الحميد بن باديس مستغانم
Keywords: الرقمنة، الخدمات الجامعية، الطلبة الجامعيين